PENGARUH TELEVISI TERHADAP PERUBAHAN BUDAYA DAN PERILAKU MASYARAKAT JAWA (Tinjauan Etika Nilai Max Scheler) - Muhaimin, Hendro (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2009)
AbstractThe ethics value of Max Scheler seems definitely lack of cultural knowledge of Javanese society which starts with local culture deficiency in television programs. Local cultures look disappear in the mass memory. When a new generation comes, they do not find the ancient culture and tradition in their daily life. MaxScheler depicts this symptom with a formation hierarchy that one is subordinate to others. The television programs influence Java society individually and socially. Finally, it is not extremely strange when the society becomes unfamiliar with traditional cultures. The society gets their confession, stutter, and powerless. The conditions lead cultural clashes and conflicts. The television programs dissolve their identity in a shallow uniformity. The society loses their ability to define their personality in attitudes and behavior. If the impacts are not quickly responded, either by the government and Javanese themselves, it could bring bad impacts to existence of the Javanese culture.Keyword: television, behavior, cultural shock.